Social conflict and harmony : tourism in China's multi-ethnic communities - Yang, Jingjing; Zhang, Lingyun; Ryan, Chris, 1945- (Tourism social science series ;, 2016)
The book examines the extent to which Coser's (1956) 16 propositions can apply to tourism impact studies and, where possible, to enhance, deepen and challenge the original theory, using evidence from communities in China that differ from the context used by Coser. The combination of ethnographic description and sociologically-oriented analysis, drawing upon both Chinese and western paradigms that are, at times very different in their underlying value system, challenges several of Coser's suppositions. The book will also draw upon subsequent publications by the authors, both severally and separately. These publications have utilised different concepts and paradigms, including for example the use of Valene Smith's concept of the 'culture broker', Turner's concepts of marginalised peoples, and the paradigms of constructionism and interpretive research work used in other studies by the authors. The sum of the work, it is suggested, adds to our canon of knowledge about social conflict in tourism development as well as impacts of tourism on disadvantaged ethnic communities in China.